Educational Systems Scenarios Development in Modern Conditions - Levina, Elena Y.; Yevgrafova, Olga G.; Derdizova, Farida V.; Levchenkova, Tatyana V.; Murugova, Vera V.; Blinova, Lyubov N.; Anfilatova, Olga V.; Zagladina, Elena N. (International Review of Management and Marketing, 2016)
The educational system is a set of nonlinear subsystems subjected by waves of exogenous and endogenous impacts. Due to the chaotic nature of the educational processes the management of the educational system’ development is significantly complicated. This article aims to develop aspects of the theory of scenario modeling in educational systems and processes. The authors highlight systemic patterns that determine the processes of development of educational systems and establish corridors of possible variability of processes, while maintaining a positive dynamics. The basic criteria for the development of alternative scenarios of educational systems, structures and processes allowing develop scenarios of educational systems’ development in an unstable external and internal environment are allocated. The types of scenarios for the development of educational systems and their possible categorical interaction are given. This article is intended for heads of educational institutions, senior managers, researchers involved in modeling and development of educational systems. Keywords: Educational Systems, Educational Processes, Management of Development, Scenarios. JEL Classifications: H11, I21, I28